Governance and Sustainable Development: The Role of Environmental Performance at the Country Level - Naz, Sana; Ditta, Allah; Ramzan, Muhammad; Abbas, Muhammad (Pakistan Journal of Humanities and Social Sciences, 2024)
The objective of this study is to examine the role of environmental performance and governance in promoting sustainable development. This study employs secondary data spanning from 2015 to 2022 from different sources, including the World Governance Indicators Index, the environmental performance of the countries, and sustainable development goals. We used Eviews-9 software and applied panel regression techniques to analyses the data. We found that there was a negative impact of governance on sustainable development, and results suggested that the governments, policy makers, and other stakeholders have to change the existing model of governance to achieve sustainable development goals. In contrast, environmental performance positively affects sustainable development, indicating that in order to achieve sustainable development goals, the government, businesses, and other stakeholders must concentrate on the environmental performance of their respective nations. Moreover, a country’s environmental performance mediates the relationship between governance and sustainable development goals. The findings indicated that environmental performance has a mediating role in achieving sustainable development and that governance alone is insufficient to do so. As a result, for the country to promote sustainable development goals, all stakeholders must support environmental protection initiatives.